Latin American central banking comes of age - Steven B. Kamin; John Kearns (American Enterprise Institute (AEI), 2021)
A persistent issue for central banks in emerging market economies (EMEs) has been their difficulties in pursuing counter-cyclical monetary policies such as those adopted in advanced economies (AEs). The flexible inflation targeting pursued by most AE central banks entails tightening monetary policy when inflation exceeds their targets, but loosening policy when economic activity declines below its equilibrium level. Such policies are generally pursued by AE central banks, even when their formal mandates are for price stability alone.In EMEs, however, loosening policy in response to weak activity has been complicated by a couple of factors. First, historically, EME recessions have been triggered by financial crises, which often have been the product of investor worries about excessively lax macroeconomic policies. Therefore, even in the face of sharp recessions, EME central banks frequently have been forced to tighten policy in order to bolster investor confidence and restrain exchange rate depreciations and capital outflows that threaten to further undermine financial stability. Second, and as a related matter, in EMEs with histories of high and poorly-anchored inflation, even small and transitory increases in inflation had to be curtailed through monetary tightening before they could translate into higher inflation expectations and, again, investor worries about macroeconomic management. These considerations have applied with particular force in Latin America, given its long history of high inflation and even hyperinflation.
Keywords: A; 330; Central Bank; International Economy; Latin America